2012
DOI: 10.1097/igc.0b013e318256e5e4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Several Cervical Screening Strategies for Early Detection of Cervical Cancer: A Meta-Analysis

Abstract: This meta-analysis suggests that LBC appeared to be promising in primary cervical cancer screening in resourced regions, and VILI might be a good choice to identify/exclude cervical cancerous and precancerous lesions in resource-constrained regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 52 publications
8
27
3
2
Order By: Relevance
“…Subsequently, in these regions it should be looked for others. Numerous modalities of screening are currently accessible for early diagnosis of cervical cancer could be helpful in those areas [6]. Visual inspection of the cervix following application of 3-5% acetic acid (VIA) and that subsequent to the application of Lugol's iodine (VILI), have been broadly evaluated as alternative screening tests in many developing countries, because they are simple, inexpensive and feasible [7].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, in these regions it should be looked for others. Numerous modalities of screening are currently accessible for early diagnosis of cervical cancer could be helpful in those areas [6]. Visual inspection of the cervix following application of 3-5% acetic acid (VIA) and that subsequent to the application of Lugol's iodine (VILI), have been broadly evaluated as alternative screening tests in many developing countries, because they are simple, inexpensive and feasible [7].…”
Section: Introductionmentioning
confidence: 99%
“…Even though, the conventional cervical cytology has been used for a very long time, in many countries the Thin Prep test is taking its place in routine practice. Numerous meta-analysis and clinical research showed that Thin Prep test is decreasing the rate of unsatisfactory and satisfactory and more sensitive in detecting cervical cell abnormalities (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…U prilogu učešća infektivnog agensa govore i neka istraživanja u kojima je ustanovljeno da na rizik za nastanak raka grlića kod žena utiču i seksualne navike njihovih muževa tj. veći broj partnerki [8]. Relativni rizik od nastanka raka grlića materice je oko 65% veći kod žena sa pozitivnim nalazom na humani papiloma virus u odnosu na one sa negativnim nalazom, a takođe je ustanovljeno da kod žena sa hroničnom infekcijom humanim papiloma virusom, postoji 200% veći rizik od progresije normalnog Papa nalaza u cervikalnu intraepitelnu neoplaziju II ili III (CIN II i CIN III) u dvogodišnjem razdoblju, u odnosu na žene sa negativnim nalazom humanog papiloma virusa [9].…”
Section: Uvodunclassified